Difference between revisions of "009A Sample Final A, Problem 4"

From Math Wiki
Jump to navigation Jump to search
m
Line 10: Line 10:
 
|Since only two variables are present, we are going to differentiate everything with respect to <math style="vertical-align: 0%">x</math> in order to find an expression for the slope, <math style="vertical-align: -21%">m = y' = dy/dx</math>. Then we can use the point-slope equation form <math style="vertical-align: -21%;">y-y_{1} = m(x-x_{1})</math> at the point <math style="vertical-align: -21%">\left(x_1,y_1\right) = (1,1)</math> to find the equation of the tangent line.
 
|Since only two variables are present, we are going to differentiate everything with respect to <math style="vertical-align: 0%">x</math> in order to find an expression for the slope, <math style="vertical-align: -21%">m = y' = dy/dx</math>. Then we can use the point-slope equation form <math style="vertical-align: -21%;">y-y_{1} = m(x-x_{1})</math> at the point <math style="vertical-align: -21%">\left(x_1,y_1\right) = (1,1)</math> to find the equation of the tangent line.
 
|-
 
|-
|Note that implicit differentiation will require the product rule <u>''and''</u> the chain rule.  In particular, differentiating <math style="vertical-align: -18%">2xy</math> must be treated as  
+
|Note that implicit differentiation will require the product rule <u>''and''</u> the chain rule.  In particular, differentiating <math style="vertical-align: -18%">2xy</math> can be treated as  
 
|-
 
|-
 
|&nbsp;&nbsp;&nbsp;&nbsp; <math>(2x)\cdot (y),</math>
 
|&nbsp;&nbsp;&nbsp;&nbsp; <math>(2x)\cdot (y),</math>

Revision as of 21:57, 26 March 2015


4. Find an equation for the tangent line to the function   at the point .

Foundations:  
Since only two variables are present, we are going to differentiate everything with respect to in order to find an expression for the slope, . Then we can use the point-slope equation form at the point to find the equation of the tangent line.
Note that implicit differentiation will require the product rule and the chain rule. In particular, differentiating can be treated as
    
which has as a derivative
    

Finding the slope:  
We use implicit differentiation on our original equation to find
    
From here, I would immediately plug in (1,1) to find y ':
     , or

Writing the Equation of the Tangent Line:  
Now, we simply plug our values of and  into the point-slope form to find the tangent line through is
    
or in slope-intercept form
    

Return to Sample Exam